PENGGUNAAN MEDIA PAPAN MULTI FUNGSI DALAM MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN MATEMATIKA - Kadullah, Putri; Otaya, Lian Gafar; Djafar, Fatimah (DIRASATUL IBTIDAIYAH, 2024)
AbstractThis research aims to determine the improvement in learning outcomes of class V students at SDN 7 Limboto in the material of the Least Common Multiple and the Greatest Common Factor in Mathematics Subjects. This research method is Class V Action which is carried out in a class to determine the consequences of the action applied to a research subject in that class. The subjects of this research were class V of SDN 7 Limboto, totaling 18 students. The Classroom Action Research (PTK) model that will be carried out refers to the Kemmis and Taggart model which consists of stages, namely: planning, action, observation and reflection. The results of this research indicate that the application of multi-functional board media can improve student learning outcomes in the material on Least Common Multiple and Greatest Common Factor. In the first cycle, the learning outcomes of 8 students who completed were 44.4% in the "very poor" category and 10 students who did not complete were 55.5%. In cycle II, student learning outcomes reached 83.3% in the "good" category. There were 15 students who completed and 3 students did not complete. This research can be said to be successful if it has reached the success indicator, namely 75% and this research can be said to be successful with a percentage of 83.3% in the "good" category, so this research needs to be continued in the next cycle. Keywords: Learning; Use of Multi-Function Board Media; Mathematics.